Drama As a Presentation of Self: Exploring the Evolution of Western Theatre (Journal of Advances and Scholarly Researches in Allied Education, 2012)
TheHistory of Drama, in the strict sense of the history of Western theatre,beginning from Greek times to the times of the Absurd theatre, has beenreviewed by several scholars such as Sylven Bamet, Morton Berman and WilliamBurto (1972), Irving Deer and Harriet A.